The experience of industrial (innovation) clusters of Canada - Коніжай, Роман Омельянович; Коніжай, Мар'яна Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The experience of industrial (innovation) clusters in Canada and their role in the development of scientificand technological potential. The separate results of creating free economic zones as alternative forms of stimulationof entrepreneurial activity in depressed regions and their feasibility.